1992
DOI: 10.1136/oem.49.12.845
|View full text |Cite
|
Sign up to set email alerts
|

Contact with pigs and cats associated with high prevalence of Toxoplasma antibodies among farmers.

Abstract: Antibodies to Toxoplasma were measured by enzyme linked immunosorbent assay (ELISA) in sera from 159 abattoir workers, 142 pig farmers, and 106 grain or berry farmers. Farmers occupationally exposed to pigs had antibodies in 53 (37%) cases, abattoir workers in 40 (25%) cases, and farmers not exposed to pigs in 24 (23%) cases. In each group antibodies were more prevalent among those who had a cat or cats in the household. Controlling for age and cat contacts changed the prevalences less than one percent. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
2
13
1
Order By: Relevance
“…Colnparisons of the prevalence of antibodies to toxoplasma among veterinarians and other workers have not suggested an increased risk, however, except for veterinarians in large-animal practice (13). They may have an increased risk through mucous membrane contact with blood or the excretions of infected animals, while helping with labor and while making field autopsies (14).…”
Section: Discussionmentioning
confidence: 99%
“…Colnparisons of the prevalence of antibodies to toxoplasma among veterinarians and other workers have not suggested an increased risk, however, except for veterinarians in large-animal practice (13). They may have an increased risk through mucous membrane contact with blood or the excretions of infected animals, while helping with labor and while making field autopsies (14).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to cats and cat feces has been considered a major risk factor for acquisition of infection. However, while several studies have concluded that exposure to cats increased the risk of T. gondii seropositivity, [19][20][21][22][23][24][25][26] other studies found no association, [27][28][29][30][31][32][33][34] and one study 35 found that possession of cats decreased this risk. Exposure to cats is not sufficient for transmission of T. gondii infection to humans; infection in cats and personal hygiene should also be evaluated.…”
mentioning
confidence: 99%
“…Whereas contact with soil and gardening have been implicated as risk factors for T. gondii seropositivity, 19,26 several studies have found no association between soil contact and seropositivity. 25,34 The role of handling or consumption of raw meat in the acquisition of T. gondii infection has not always been clear. Several studies have found no association, 21,25,28,33 although some studies have identified an association between eating raw meat and T. gondii seropositivity, 32,34 and handling of raw organ meats used for pet food has been identified to increase the risk of T. gondii infection in men.…”
mentioning
confidence: 99%
See 2 more Smart Citations